Diagnosis of bovine herpesvirus-l (BHV-l) infection in aborting cattle and buffaloes by virus isolation and polymerase chain reaction (PCR) - DRAMI, J S; DWIVEDI, P N; ., RAMNEEK; DEKA, DIPAK; MAITI, N K; OBEROI, M S (The Indian Journal of Animal Sciences, 2011)
Sera samples (50) from cattle and buffaloes with the history of abortion from 2 dairy farms of Punjab were screened for BHV-1 antibody by using avidin-biotin ELISA (AB-ELISA) that revealed an overall prevalence rate of 72%. The seroprevalence of BHV-1 in cattle and buffaloes was 85.70 and 54.50%, respectively. Subsequently, double antibody sandwich ELISA (DAS-ELISA), virus isolation and peR were carned out to detect BHV-1 in aborted placental tissues. A marked difference was observed between the proportion of peR positive and DAS-ELISA and virus isolation positive sanlples, suggesting peR to be more sensitive method for detection ofBHV-1 in aborted placental tissue.Â